(untitled) (Chemical Bulletin of Kazakh National University, 2025)
The study focuses on the synthesis and pharmacological evaluation of novel structural analogs of the anesthetic and antiarrhythmic Kazcaine. Two new derivatives were synthesized by acylation of propylacetylene alcohol 1-(2-ethoxyethyl)-4-oxopiperidine with fluorobenzoyl chlorides. Their complexes with cyclodextrin were obtained for biological screening. The evaluation of the myelostimulating activity of these complexes revealed that one of them, specifically the 3-fluorobenzoyloxy derivative, demonstrated a pronounced myelostimulating effect, particularly with regard to the stimulation of leukopoiesis and thrombopoiesis. The compound, in complex with β-cyclodextrin, showed significant stimulation of leukocyte and platelet proliferation, with a noticeable increase in the total number of leukocytes and improvement in granulocyte and lymphocyte recovery. These results indicate that the synthesized compounds have significant potential for pharmacological use, especially for stimulating hematopoiesis and protecting against myelosuppression. In addition, quantum chemical calculations of the reactions showed that ortho- and meta-fluorobenzoyl chloride have higher reactivity, which is confirmed by the high yields of the products (94% and 89%) obtained as a result of the synthesis.